Development of a UHPLC method for the detection of organic gunshot residues using artificial neural networks. Issue 18 (21st September 2015) - Taudte, Regina Verena; Roux, Claude; Bishop, David; Blanes, Lucas; Doble, Philip; Beavis, Alison
<x xml:space="preserve">Abstract</x> A UHPLC method was developed for a broad range of OGSR compounds using ANNs and evaluated using simulated case samples.